Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858384
|View full text |Cite
|
Sign up to set email alerts
|

Usability and Security of Text Passwords on Mobile Devices

Abstract: Recent research has improved our understanding of how to create strong, memorable text passwords. However, this research has generally been in the context of desktops and laptops, while users are increasingly creating and entering passwords on mobile devices. In this paper we study whether recent password guidance carries over to the mobile setting. We compare the strength and usability of passwords created and used on mobile devices with those created and used on desktops and laptops, while varying password p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…• Password based authentication, sometimes called an alphanumeric passcode: where a user is asked to recall a standard text-based password (entered using a so -keyboard) to unlock the device. e usability and security of PINs [9,40], pa erns [4,36] and passwords [22,29] have been well documented by researchers. Beyond these methods, picture-based [46] and biometric based mechanisms are also used to unlock mobile devices.…”
Section: Background and Related Workmentioning
confidence: 99%
“…• Password based authentication, sometimes called an alphanumeric passcode: where a user is asked to recall a standard text-based password (entered using a so -keyboard) to unlock the device. e usability and security of PINs [9,40], pa erns [4,36] and passwords [22,29] have been well documented by researchers. Beyond these methods, picture-based [46] and biometric based mechanisms are also used to unlock mobile devices.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In addition, the properties of the authentication device play a major role in this process. The authors of [159] investigated the usability of textual passwords on mobile devices. It was proven that using a smartphone or other keyboardless equipment for creating a password suffers from poor usability as compared to conventional personal computers.…”
Section: Usabilitymentioning
confidence: 99%
“…Despite the significant advancements in authentication on smartphones and tablets, text passwords continue to be one of the most widely used schemes on handheld mobile devices. They are often used when accessing services such as emails, online banking, e-shopping, and more [21].…”
Section: Introductionmentioning
confidence: 99%
“…Entering text passwords on mobile devices is not only error prone and time consuming [13,21,23], but also subject to shoulder surfing [4,27]. Melicher et al reported that users take 20% longer to enter passwords on mobile devices, and made twice as many errors [21].…”
Section: Introductionmentioning
confidence: 99%